PENGARUH LAJU KOROSI PELAT BAJA LUNAK PADA LINGKUNGAN AIR LAUT TERHADAP PERUBAHAN BERAT. - Hartono, Hartono (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2008)
One of the usage of soft steel sheet at human life among others as boat sheet. Existence of electrochemical reaction between metal and environment can cause the corrosion. Corrosion represent an situation having the destroying nature at most of all metal. Trial of rate of corrosion at soft steel sheet to sea water can be conducted by using overvoltage. Heavy change (losing of weight) of specimen will be progressively increase by increasing its test time.